Study on the Ecological Interaction Mechanism of Continuous Cropping Soil Driven by Different Modifiers - Juan Wang; Yuanyuan Wang; Wei Tan; Dan Zhao; Chunmei Xu; Zhiwei Wang; Yufeng Liu; Siyu Liu; Jiayi Kang (Horticulturae)
In this study, the effects of different modifiers on rhizosphere soil microorganisms, their functions, and the soil properties of continuous tomato cropping were investigated. Nine amendments were selected to treat the soil from a 14-year continuous tomato cropping system. Tomato yield, soluble solids, soil physical and chemical properties, and soil enzyme activities were measured. Changes in soil microbial community structure and function were determined by metagenomic sequencing, and their correlation with environmental factors was analyzed. The results showed that among the nine amendments, the combination of farmyard manure + Bacillus subtilis + Trichoderma harzianum (T2) and plant-derived straw decomposed soil + Bacillus subtilis + Trichoderma harzianum (T3) had the most significant effects. The tomato yield, soil hydrolyzable nitrogen, available phosphorus, available potassium, organic matter, and total nitrogen contents and soil phosphatase activities were significantly increased under the T2 and T3 treatments. Compared with the CK treated with T2, the contents of yield, alkali-hydrolyzed nitrogen, available phosphorus, available potassium, organic matter, and total nitrogen were significantly increased by 34.46%, 41.84%, 52.44%, 45.01%, 24.5%, and 41.18%, respectively. The soil microbial community structure also changed significantly. The relative abundance of Proteobacteria, Chloroflexi, and Bacteroidota increased significantly. The relative abundance of Hyphomicrobium, Rhodomicrobium, and Rhodoplanes increased significantly compared with the control. The soil microbial function was mainly enriched in two pathways of amino acid metabolism and carbohydrate metabolism. Among them, T2 significantly enriched six community functions, such as bacterial chemotaxis. T3 significantly enriched three community functions, such as glutathione metabolism. A correlation analysis showed that soil hydrolyzable nitrogen, available phosphorus, pH, phosphatase, and catalase were the key factors affecting microbial community changes. The treatment of farm manure/plant-derived straw decomposed soil + Bacillus subtilis + Trichoderma harziensis improved the soil environment, increased crop yield, clarified the effects of different modifiers on the functional mechanisms of the soil microbial community, and provided a practical solution to the problem of soil degradation in agriculture monoculture.